1951
DOI: 10.1037/h0059488
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of anxiety to the conditioned eyelid response.

Abstract: Stale Uii&eriity cf IowaA number of contemporary psychological theorists, such as Hull (2)j .Tolman (9), and Lewin (5), are in agreement that behavior is a function of'two principle ; classes of variables: learning or cognitive on the one band; and motivation on the other. These classes of variables are further conceived by Hull (2) as combining according to some multiplicative function, implying that a zero value of either will lead to failure of response occurrence. Hull has specifically pro-.posed the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
277
0
3

Year Published

1954
1954
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 360 publications
(291 citation statements)
references
References 9 publications
(5 reference statements)
11
277
0
3
Order By: Relevance
“…In more complex learning tasks, where there are several competing responses, the advantage will be with the low anxiety group. The prediction has veen verified in experiments with adults using both classical conditioning (Taylor, 1951 ;Spence and Taylor, 195 1 ;Spence and Farber, 1953) and more complex forms of learning (Taylor and Spence, 1952 ;Farber and Spence, 1953 , Montague, 1953 ;Spence, Farber and McFann, 1956 If the theory is extrapolated to apply to grammar and secondary modern school groups, the prediction will presumably be that, since academic learning is a complex matter at which grammar school children meet with greater success, grammar school children will have a lower level of anxiety than secondarv modern school children. This prediction directly opposes that made from Davis's theory and runs counter to Bene's findings, unless the two theories are concerned with different kinds of anxiety.…”
Section: (B) Anxiety and Learningmentioning
confidence: 84%
“…In more complex learning tasks, where there are several competing responses, the advantage will be with the low anxiety group. The prediction has veen verified in experiments with adults using both classical conditioning (Taylor, 1951 ;Spence and Taylor, 195 1 ;Spence and Farber, 1953) and more complex forms of learning (Taylor and Spence, 1952 ;Farber and Spence, 1953 , Montague, 1953 ;Spence, Farber and McFann, 1956 If the theory is extrapolated to apply to grammar and secondary modern school groups, the prediction will presumably be that, since academic learning is a complex matter at which grammar school children meet with greater success, grammar school children will have a lower level of anxiety than secondarv modern school children. This prediction directly opposes that made from Davis's theory and runs counter to Bene's findings, unless the two theories are concerned with different kinds of anxiety.…”
Section: (B) Anxiety and Learningmentioning
confidence: 84%
“…In intriguing observations, Berry and associates reported that if training trials (rabbits-delay eyeblink) were given during episodes of hippocampal frequency slow waves, learning was substantially faster than if such trials were given during episodes of non-activity (Seager et al 2002). Stress also enhances acquisition in rats (Shors 1998), as does anxiety in humans (Taylor 1951). Actually, stress enhances acquisition in male rats but impairs it in females (Shors et al , 2000Wood and Shors 1998;Shors 2001).…”
Section: Modulatory Effects On Eyeblink Conditioningmentioning
confidence: 99%
“…In addition, long-term practice effects were also observed: s-IgA secretion rate increased significantly from day 1 to day 22. These changes in s-IgA secretion rate appeared to be independent of psychological distress, since no change was observed in anxiety as measured by the anxiety scale on the Hopkins symptom checklist (Derogatis et al, 1974) and the Taylor manifest anxiety scale (Taylor, 1951). jasnoski and Kugler (1987) randomly assigned 30 undergraduates to two relaxation groups or a control group.…”
Section: Relaxation and Imagerymentioning
confidence: 99%